1997
DOI: 10.1016/s0735-1097(97)00256-8
|View full text |Cite
|
Sign up to set email alerts
|

Angina-Induced Protection Against Myocardial Infarction in Adult and Elderly Patients: A Loss of Preconditioning Mechanism in the Aging Heart?

Abstract: The presence of angina before acute myocardial infarction seems to confer protection against in-hospital outcomes in adults; this effect seemed to be less obvious in elderly patients. This study suggests that the protection afforded by angina in adult patients may involve the occurrence of ischemic preconditioning, which seems to be lost in senescent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
2
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 32 publications
4
112
2
8
Order By: Relevance
“…Other studies assessing PIA in the elderly used different definitions and included patients with more advanced age, but achieved results similar to those of this subset of patients regarding the absence of the protective effect of PIA 10,11 . Our sample was predominantly male, in agreement with literature data, which report higher prevalence of AMI in this population 6,10,11,13 , as well as greater risk for developing AMI 14 .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Other studies assessing PIA in the elderly used different definitions and included patients with more advanced age, but achieved results similar to those of this subset of patients regarding the absence of the protective effect of PIA 10,11 . Our sample was predominantly male, in agreement with literature data, which report higher prevalence of AMI in this population 6,10,11,13 , as well as greater risk for developing AMI 14 .…”
Section: Discussionmentioning
confidence: 58%
“…This result was independent of thrombolytic therapy, even with the PIA group receiving more lytic therapy than the non-PIA group. After logistic regression analysis for potential confounders, the results remained unchanged 11 . Based on animal model studies showing that caloric restriction restored IPC, the same authors assessed the influence of body mass index (BMI) on the protective effect of PIA in the elderly and concluded that such protection was preserved only in the subset of elderly patients with the lowest BMI 23 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…P. Abete et al [40] обнаружили, что у пациентов мо-лодого и среднего возраста, отмечавших наличие стенокардии до развития инфаркта миокарда, на-блюдался низкий процент развития кардиогенно-го шока, застойной сердечной недостаточности и внутригоспитальной смертности, что рассматри-валось авторами как проявление ИП. У пациентов 60-65 лет авторы наблюдали угнетение процессов ишемического прекондиционирования в миокарде.…”
Section: Aadsorasunclassified